Aprendizaje organizacional y gestión educativa en la unidad “Ramón Barba Naranjo”. diseño de una metodología para el desarrollo del aprendizaje organizacional. - Villarroel Scotland, Blanca Nieves (2020)
As a result of social evolution, organizations tend to incorporate knowledge, and organizational learning as mechanisms that generate intangible assets, knowledge and information are always present at Society dynamic and Educational Management, based on these reflections, this research work described since various perspectives the development of organizational learning as management form; characterizing the management applied by “Ramón Barba Naranjo” Educational Unit and established a methodology for organizational learning development at this institution. Methodologically, a qualitative approach was applied through hermeneutics in order to interpret the obtained information through semi-structured interviews to campus authorities. The existence of factors that limit the implementation of organizational learning was determined, as resistance to change, conformism and disinterest, negative leaders, non-integrating perspectives, individual working and the Ministry of Education role, among others. Finally, a proposal was made to developed organizational learning as an impetus for educational management in this campus.